Pseudothrombophlebitis in a patient with Behcet's syndrome: Doppler ultrasound and magnetic resonance imaging findings - Ozgocmen, S; Kocakoc, E; Kiris, A; Ardicoglu, O (Springer-Verlag, 2002)
A 33-year-old man with a known diagnosis of Behcet's syndrome (BS), presented with pseudothrombophlebitis resulting from acute rupture of a popliteal cyst. Doppler ultrasound and magnetic resonance imaging findings are explained. Differentiation of rupture of a Baker's cyst from true thrombophlebitis, especially in patients with BS, who are potentially susceptible to thrombotic events, is extremely important.
Keywords: Baker's cyst; Behcet's syndrome; pseudothrombophlebitis